Prevalence and Prognostic Significance of Preoperative Anemia in Radical Cystectomy Patients: A Multicenter Retrospective Observational Study - Ernest Kaufmann; Luca Antonelli; Luca Afferi; Vincenzo Asero; Francesco Prata; Silvia Rebuffo; Alessandro Veccia; Meftun Culpan; Karl Tully; Luis Ribeiro; Thierry Roumeguere; Kees Hendricksen; et al. (European Urology Open Science)
Background and objective: Preoperative anemia is common in patients undergoing radical cystectomy for bladder cancer, but its prevalence and impact on outcomes remain poorly characterized across different health care settings. This study aims to assess the prevalence of preoperative anemia, evaluate its current management practices, and determine its association with postoperative and oncological outcomes in patients undergoing radical cystectomy. Methods: We retrospectively analyzed 4886 patients with nonmetastatic bladder cancer who underwent radical cystectomy across 28 centers in 13 countries. Multivariable regression models identified the predictors of preoperative hemoglobin levels and postoperative blood transfusions. Survival outcomes were assessed using Kaplan-Meier and Cox proportional hazards regression analyses. Key findings and limitations: Preoperative anemia was present in 44% of women and 48% of men. Among anemic patients, 73% received no blood management interventions. Higher hemoglobin levels before transurethral resection of a bladder tumor correlated with higher levels before cystectomy and fewer postoperative blood transfusions (odds ratio: 0.98, 95% confidence interval [CI]: 0.97–0.99, p < 0.001). Higher preoperative hemoglobin levels were associated with lower 90-d mortality rates (hazard ratio: 0.98, 95% CI: 0.97–0.99, p < 0.001) and independently predicted reduced all-cause mortality, cancer-specific mortality, and disease relapse. Conclusions and clinical implications: Preoperative anemia is prevalent and undertreated in patients undergoing radical cystectomy, and is independently associated with adverse perioperative and oncological outcomes. This highlights the need for further research regarding the potential benefits of implementing systematic preoperative anemia management. Patient summary: This study found that low blood counts before bladder removal surgery are common, often untreated, and linked to worse outcomes. Early treatment of low blood counts before surgery could improve results for patients.